Herpes zoster vaccination and dementia occurrence - Pomirchy, Michael; Bommer, Christian; Pradella, Fabienne; Michalik, Felix; Peters, Ruth; Geldsetzer, Pascal (The journal of the American Medical Association, 2025)
Recent evidence from a quasi-experiment in Wales showed that herpes zoster (HZ) vaccination appears to prevent or delay dementia. Exploiting a similar quasi-experiment in Australia, this study investigated the effect of HZ vaccination on dementia occurrence in a different population and health system setting.To determine the effect of HZ vaccination on the probability of receiving a new diagnosis of dementia.In Australia, starting November 1, 2016, live attenuated HZ vaccination was provided free to individuals aged 70 to 79 years through primary care clinicians. Thus, individuals whose 80th birthday was just a few weeks before November 1, 2016, never became eligible, whereas those whose 80th birthday was just a few weeks later were eligible. The key strength of this quasi-experiment is that one would not expect that these comparison groups who differ in age only minutely would, on average, differ in any health characteristics and behaviors. Primary health care records were analyzed with week-of-birth information from 65 general practices across Australia, using a regression discontinuity design.Eligibility for HZ vaccination based on date of birth.New diagnoses of dementia as recorded in primary care electronic health record data.In this sample of 101219 patients, 52.7% were women and mean age was 62.6 years (SD, 9.3 years) as of November 1, 2016. Individuals born just before vs just after the date-of-birth eligibility threshold (November 2, 1936) for HZ vaccination were well balanced in their past preventive health services uptake and past chronic disease diagnoses. There was an abrupt increase of 16.4 percentage points (95% CI, 13.2-19.5; P < .001) in the probability of ever receiving HZ vaccination between patients born shortly before vs shortly after the date-of-birth eligibility threshold. The eligibility rules of the HZ vaccination program thus created comparison groups born just on either side of the date-of-birth eligibility threshold who were likely similar to each other, except for a large difference in their probability of receiving the intervention (HZ vaccination) of interest. This study found that eligibility for HZ vaccination (ie, being born shortly after vs shortly before November 2, 1936) decreased the probability of receiving a new dementia diagnosis during 7.4 years by 1.8 percentage points (95% CI, 0.4-3.3 percentage points; P = .01). Being eligible for HZ vaccination did not affect the probability of taking up other preventive health services (including other vaccinations) or the probability of receiving a diagnosis of common chronic conditions other than dementia.By taking advantage of a quasi-experiment and corroborating findings from Wales in a different population, this study provides evidence of the potential benefits of HZ vaccination for dementia that is more likely to be causal than that of more commonly conducted associational studies.
Gesehen am 18.02.2026